2009
DOI: 10.1055/s-0029-1212128
|View full text |Cite
|
Sign up to set email alerts
|

Administration of glycyrrhetinic acid: significant correlation between serum levels and the cortisol/cortisone-ratio in serum and urine

Abstract: In vitro, cortisol and aldosterone have a similar affinity to the mineralocorticoid receptor. The 11beta-hydroxysteroid dehydrogenase catalyzes the interconversion of cortisol to its inactive 11-oxo-metabolite cortisone. This interconversion is responsible for the in vivo specificity of the mineralocorticoid receptor. A defect of this enzyme leads to a pseudohyperaldosteronism with hypertension and hypokalemia, the so-called apparent mineralocorticoid excess syndrome. Glycyrrhetinic acid, a compound of licoric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…The measurement of the urinary free cortisol-cortisone ratio has been reported to be a sensitive indicator of renal 11 β-HSD 2 activity (Palermo et al, 1996;Heilmann et al, 1999). This enzyme is essential for maintaining corticoid hypokalemia with hypertension being the major symptom (Quinkler and Stewart, 2003).…”
Section: Clinical Relevance Of the Urinary Free Cortisol/cortisone Ratiomentioning
confidence: 99%
“…The measurement of the urinary free cortisol-cortisone ratio has been reported to be a sensitive indicator of renal 11 β-HSD 2 activity (Palermo et al, 1996;Heilmann et al, 1999). This enzyme is essential for maintaining corticoid hypokalemia with hypertension being the major symptom (Quinkler and Stewart, 2003).…”
Section: Clinical Relevance Of the Urinary Free Cortisol/cortisone Ratiomentioning
confidence: 99%
“…The serum cortisol-to-cortisone (F/E) ratio is a marker of net 11βHSD activity [14] , which changes in some settings, such as inflammatory conditions [15] or after the administration of the 11βHSD2 inhibitor found in licorice [14] . If dysregulated cortisol metabolism contributes to OAH, then the F/E ratio might correlate with BP in obese patients, and changes in the F/E ratio might parallel BP reductions during weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have reported that GA induces sodium retention, hypokalemia and hypertension, which are symptoms of pseudoaldosteronism, in clinical and experimental studies Serra et al, 2002;Monder et al, 1989) and also an elevation of the cortisol/cortisone-ratio in serum and urine in healthy volunteers (Heilmann et al, 1999). It is also well known that GA inhibits human 11β-hydroxysteroiddehydrogenase (11β-HSD) (Bujalska et al, 1997).…”
Section: Introductionmentioning
confidence: 99%